2017
DOI: 10.1038/srep41040
|View full text |Cite
|
Sign up to set email alerts
|

Comparative genomics and transcriptome analysis of Aspergillus niger and metabolic engineering for citrate production

Abstract: Despite a long and successful history of citrate production in Aspergillus niger, the molecular mechanism of citrate accumulation is only partially understood. In this study, we used comparative genomics and transcriptome analysis of citrate-producing strains-namely, A. niger H915-1 (citrate titer: 157 g L −1 ), A1 (117 g L −1 ), and L2 (76 g L −1 )-to gain a genome-wide view of the mechanism of citrate accumulation. Compared with A. niger A1 and L2, A. niger H915-1 contained 92 mutated genes, including a succ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
60
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
2
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(63 citation statements)
references
References 62 publications
3
60
0
Order By: Relevance
“…In agreement with (Ratledge, 2000 ; Ratledge and Ruijter, 2000 ; Ruijter et al, 2000 ; Yin et al, 2017 ), we found that the difference in extracellular citrate accumulation was remarkably independent of citA expression; the gene was not differentially expressed between NW186 −Fe and NW305 −Fe (Table 3 , Figure 7 ). Most remarkably, though, citA was overexpressed in both NW186 −Fe and NW305 −Fe compared to NW305 ++Fe, while citrate metabolizing enzymes aconitase (EC 4.2.1.3) and NADP-IDH (EC 1.1.1.42) did not show iron-dependent transcriptional regulation (Table 3 , Figure 7 ).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In agreement with (Ratledge, 2000 ; Ratledge and Ruijter, 2000 ; Ruijter et al, 2000 ; Yin et al, 2017 ), we found that the difference in extracellular citrate accumulation was remarkably independent of citA expression; the gene was not differentially expressed between NW186 −Fe and NW305 −Fe (Table 3 , Figure 7 ). Most remarkably, though, citA was overexpressed in both NW186 −Fe and NW305 −Fe compared to NW305 ++Fe, while citrate metabolizing enzymes aconitase (EC 4.2.1.3) and NADP-IDH (EC 1.1.1.42) did not show iron-dependent transcriptional regulation (Table 3 , Figure 7 ).…”
Section: Discussionsupporting
confidence: 91%
“…As a response to this work, this was later attributed to the activity of CitA within unmodified cells already being well above the activity which would account for the observed rate of A. niger citrate production (Ratledge, 2000 ; Ratledge and Ruijter, 2000 ). In another instance, the two mitochondrial citrate synthases in A. niger H915-1 were even found to be down-regulated during the citrate production phase (Yin et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It should be noted that hyper producing strains, reaching over 100 g·L -1 , have been evolved from very similar genetic background. The resulting strains have structural genomic re-arrangements but with the same set of genes, except for mutations in genes involved in citrate production [32].…”
Section: Resultsmentioning
confidence: 99%
“…A more recent study also used PCA analysis (however, for transcriptomics data) to characterize expression differences between wild‐type and citrate‐producing Aspergillus niger strains. Candidate upregulated transporter enzymes identified in this study were targeted for genetic manipulation in a later work resulting in a fivefold increase in citric acid production over the wild type .…”
Section: Review Of Instances Of Data‐driven Me Effortsmentioning
confidence: 99%